DIABETIC RETINOPATHY, FREQUENCY, SEVERITY, AND RISK CORRELATES AT DIR LOWER (The Research of Medical Science Review, 2025)
To determine the frequency and severity of DR in people aged 30 and older, this community-based cross-sectional survey was conducted in several rural and urban regions of District Dir Lower, Khyber Pakhtunkhwa, Pakistan, between June 2024 and March 2025. All 697 patients underwent a thorough eye examination that included dilated funduscopy, intraocular pressure measurement, and fundus imaging where necessary. With 92.7% having non-ins positive Dependent Diabetes Mellitus (NIDDM) and 7.3% having Insulin Dependent Diabetes Mellitus (IDDM), there were 110 people (15.8%) with diabetes. The prevalence of diabetic retinopathy was 15.4%, and it was considerably higher in patients with IDDM (50%) and in those who had had diabetes for more than ten years. While severe DR, proliferative DR, and maculopathy were less frequent, mild and moderate, non-proliferative DR accounted for the majority of DR cases. DR was more common in men, although diabetes was more common in women (59.1%). The prevalence of DR was also linked to occupation and length of disease, with individuals with longer durations of diabetes and those who were working experiencing higher rates. Some individuals needed more regular follow-ups or interventions (such as laser treatment), although the majority merely received yearly follow-ups. These findings emphasize the need for continuous diabetes management, preventative intervention, and routine DR screening, especially in semi-rural locations where access to specialized care may be limited.